Cyclic torsion very high cycle fatigue of VDSiCr spring steel at different load ratios. (January 2015) - Mayer, H.; Schuller, R.; Karr, U.; Irrasch, D.; Fitzka, M.; Hahn, M.; Bacher-Höchst, M.
Highlights: A method for ultrasonic torsion fatigue testing at positive load ratios is shown. A Haigh diagram for cyclic torsion loading up to the VHCF regime is presented. Cyclic torsion HCF and VHCF properties are strongly influenced by the load ratio. Mean stress sensitivity of shot-peened VDSiCr spring steel for −1 ⩽  R  ⩽ 0.5 is M  = 0.33. VHCF cracks preferentially start in the matrix below the surface compressive area. Abstract: Cyclic torsion fatigue tests with superimposed static torsion loads are performed with VDSiCr spring steel with shot-peened surface in the high cycle fatigue (HCF) and very high cycle fatigue (VHCF) regime. Fatigue properties are investigated at load ratios R  = 0.1, R  = 0.35 and R  = 0.5 up to limiting lifetimes of 5 × 10 9  cycles with a newly developed ultrasonic torsion testing method. Increasing the load ratio reduces the shear stress amplitude that the material can withstand without failure. Fatigue cracks are initiated at the surface in the HCF regime. In the VHCF regime, cracks are preferentially initiated internally in the matrix, below the surface layer with compression residual stresses, and less frequently at the surface. Cyclic and mean shear stresses with 50% survival probability in the VHCF regime are presented in a Haigh diagram. Linear line approximation delivers a mean stress sensitivity of M  = 0.33 for load ratios between R  = −1 and R  = 0.5.